Arctic stratosphere changes in the 21st century in the Earth system model SOCOLv4 - Vargin, Pavel; Kostrykin, Sergey; Koval, Andrey; Rozanov, Eugene; Egorova, Tatiana; Smyshlyaev, Sergey; Tsvetkova, Natalia (Frontiers in Earth Science, 2023)
Two ensemble simulations of new Earth system model SOCOLv4 over the 2015 - 2099 under moderate (SSP2-4.5) and severe (SSP5-8.5) scenarios of GHG emissions growth were analyzed to investigate changes in key dynamical processes relevant for Arctic stratospheric ozone. The model shows a 5–10 K cooling and 5-20% humidity increases in the lower - upper stratosphere in March (when the most considerable ozone depletion may occur) between the 2080-2099 and 2015-2034 periods. In the late 21st century, the strengthening of zonal mean meridional heat flux up to 20 K m/s (~25%) in the upper stratosphere nearby 70°N in January–February is obtained under SSP2-4.5 while only a slight increase over 50°N-60°N up to 5 K m/s in the upper stratosphere and a decrease with the comparable values over the high latitudes is revealed under SSP5-8.5. Although the model simulations confirm the expected ozone recovery, particularly total ozone minimum values inside the polar cap in March through the 21st century are characterized by a positive trend in both scenarios, the large scale negative ozone anomalies up to -100 DU and comparable to the second lowest ones in March 2011 but weaker than record values in March 2020 are possible till the late 21st century. The volume of low stratospheric air with temperatures below solid nitric acid trihydrate polar stratospheric clouds (PSC NAT) formation threshold is reconstructed from 3D potential vorticity and temperature fields inside the polar vortex. It is shown a significant positive trend in this parameter in March in the SSP5-8.5 scenario. An increase in the polar vortex isolation indicate its possible strengthening in the lower stratosphere. Positive trends of surface area density of PSC NAT particles in March in the lower stratosphere over the 2015-2099 is significant under SSP5.8-5. The polar vortex longitudinal shift toward Northern Eurasia is expected in the lower stratosphere in the late 21st century in both scenarios. The statistically significant long term stratospheric sulfuric acid aerosols trend in March is expected only under SSP5.8-5. Both scenarios predict an increase in the residual meridional circulation (RMC) in March by the end of the 21st century.